Loss of mutual protection between human osteoclasts and chondrocytes in damaged joints initiates osteoclast-mediated cartilage degradation by MMPs - Larrouture, Q; Cribbs, A; Rao, S; Philpott, M; Snelling, S; Knowles, H (Springer Nature, 2021)
Osteoclasts are multinucleated, bone-resorbing cells. However, they also digest cartilage during skeletal maintenance, development and in degradative conditions including osteoarthritis, rheumatoid arthritis and primary bone sarcoma. This study explores the mechanisms behind the osteoclast–cartilage interaction. Human osteoclasts differentiated on acellular human cartilage expressed osteoclast marker genes (e.g. CTSK, MMP9) and proteins (TRAP, VNR), visibly damaged the cartilage surface and released glycosaminoglycan in a contact-dependent manner. Direct co-culture with chondrocytes during differentiation increased large osteoclast formation (p < 0.0001) except when co-cultured on dentine, when osteoclast formation was inhibited (p = 0.0002). Osteoclasts cultured on dentine inhibited basal cartilage degradation (p = 0.012). RNA-seq identified MMP8 overexpression in osteoclasts differentiated on cartilage versus dentine (8.89-fold, p = 0.0133), while MMP9 was the most highly expressed MMP. Both MMP8 and MMP9 were produced by osteoclasts in osteosarcoma tissue. This study suggests that bone-resident osteoclasts and chondrocytes exert mutually protective effects on their ‘native’ tissue. However, when osteoclasts contact non-native cartilage they cause degradation via MMPs. Understanding the role of osteoclasts in cartilage maintenance and degradation might identify new therapeutic approaches for pathologies characterized by cartilage degeneration.